Kinerja Satpol Pp Lombok Tengah Pada Penertiban Penggunaan Masker Untuk Pencegahan Dan Penanggulangan Penularan Penyakit Covid-19 - Syaefullah Syaefullah; Ardhia Pramesti; Aldi Muhammad Khoir; Satria Gunawan (Jurnal Perlindungan Masyarakat: Bestuur Praesidium, 2024)
The Central Lombok Regency Government has made every effort to prevent transmission Covid-19. One of them is by issuing Regent Regulation Number 12.B of 2020 concerning the obligation to use masks in the area. To enforce the Regent's Regulations, the role and performance of the Civil Service Police Unit is needed. Satpol PP plays a very vital role because it directly interacts with the community. Starting from socialization, patrols, enforcement, to providing masks to the community.. This research aims to find out and analyze the performance of the Central Lombok Satpol PP regarding controlling the use of masks in accordance with Regent Regulation Number 12.B of 2020. This research used the teleconference method to collect data and observations carried out indirectly, namely through social media and interactive telephone calls between researchers and sources. The research results show that the Central Lombok Satpol PP already has a high work ethic seen from sufficient attendance and working according to SOPs, and understanding the status of their roles in their respective jobs.